Efficacy and safety of flurbiprofen cataplasms versus loxoprofen sodium cataplasms in knee osteoarthritis: a randomized controlled trial - Dong Li; Yinchu Cheng; Ping Yuan; Ziyang Wu; Jiabang Liu; Jinfu Kan; Kun Zhang; Zhanguo Wang; Hui Zhang; Guangwu Zhang; Tao Xue; Junxiu Jia; et al. (Chinese Medical Journal, 2023)
Abstract. Background:. Clinical trial evidence is limited to identify better topical non-steroidal anti-inflammatory drugs (NSAIDs) for treating knee osteoarthritis (OA). We aimed to compare the clinical efficacy and safety of flurbiprofen cataplasms (FPC) with loxoprofen sodium cataplasms (LSC) in treating patients with knee OA. Methods:. This is an open-label, non-inferiority randomized controlled trial conducted at Peking University Shougang Hospital. Overall, 250 patients with knee OA admitted from October 2021 to April 2022 were randomly assigned to FPC and LSC treatment groups in a 1:1 ratio. Both medications were administered to patients for 28 days. The primary outcome was the change of pain measured by visual analog scale (VAS) score from baseline to day 28 (range, 0-10 points; higher score indicates worse pain; non-inferiority margin: 1 point; superiority margin: 0 point). There were four secondary outcomes, including the extent of pain relief, the change trends of VAS scores, joint function scores measured by the Western Ontario and McMaster University Osteoarthritis Index (WOMAC), and adverse events. Results:. Among 250 randomized patients (One patient without complete baseline record in the flurbiprofen cataplasms was excluded; age, 62.8 ± 10.5 years; 61.4% [153/249] women), 234 (93.6%) finally completed the trial. In the intention-to-treat analysis, the decline of the VAS score for the 24-h most intense pain in the FPC group was non-inferior, and also superior to that in the LSC group (differences and 95% confidence interval, 0.414 (0.147-0.681); P <0.001 for non-inferiority; P = 0.001 for superiority). Similar results were observed of the VAS scores for the current pain and pain during exercise. WOMAC scores were also lower in the FPC group at week 4 (12.50 [8.00-22.50] vs. 16.00 [11.00-27.00], P = 0.010), mainly driven by the dimension of daily activity difficulty. In addition, the FPC group experienced a significantly lower incidence of adverse events (5.6% [7/124] vs. 33.6% [42/125], P <0.001), including irritation, rash and pain of the skin, and sticky hair uncovering pain. Conclusions:. This study suggested that FPC is superior to LSC for treating patients with knee OA in pain relief, joint function improvement, and safety profile.